EXPERIMENTAL DATA ON THE ROLE OF METACOGNITION IN GAINING SELF-ASSESSMENT COMPETENCE OF HIGH SCHOOL STUDENTS - FLORENTINA MOGONEA (Studia Universitatis Babes-Bolyai, 2010)
ABSTRACT. Within a learning sequence, for solving a task given by the teacher himself or assumed by the student himself, this verifies at the same time, knowledge, capacities or general abilities necessary to solve a task, but also, metacognitive knowledge, capacities and abilities, which allow him to control monitor and regulate an activity performed, achieving at the same time actions which allow him to self appreciate, self evaluate. In this study, we are analyzing the implications which the development of the metacognition has in forming the self evaluation competence of the high school student. We are presenting the results of an experimental research, within which we intended to demonstrate the dependency relationship between metacognition and evaluation.